Krioterapi Dermatologis - Yosi Ajeng Sabila (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2019)
Cryotherapy is a controlled destruction of diseased tissue using the application of low temperature. Its is a simple, effective, cost-efficient procedure with a minimal risk of complication that has been used to treat a variety of skin conditions. Cryotherapy is indicated to treat skin conditions such as benign skin tumours, acne, pigmented lesions, viral infections, inflammatory dermatoses, infectious disorders as well as malignant skin tumours. there are several cryogens that could be used such as liquid nitrogen, nitrous oxide, and carbon dioxide. Different techniques that could be used for the application of cryogens are the times spot freeze technique, the use of cryoprobe and dipstick method. Cryotherapy is a relatively safe procedure if done to appropriate patient by a trained and experienced doctor with an appropriate procedure. Complication may occur due to inappropriate patient or inappropriate procedure. Complications may be acute, subacute or chronic. There are acute complications that may occur following cryotherapy such as local pain, edema, cryoblister formation, syncope and headache. Subacute complication that may occur are hemorrhagic necrosis, wound infection, delayed woudnd healing, temporary scar hypertrophy and subcutaneous emphysema. Whereas common chronic complication such as hypopigmentation, local hypoaesthesia, milia formation and alopation can potentially happen.